Reflexões e observações sobre as novas diretrizes curriculares e a sua influência na formação inicial do professor na universidade - Silva, Juliana Bastida da [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
With reference to curricular changes proposed by the CNE Resolution 1 /2002 and CNE 2/2002 on Teacher Education in Basic Education teaching degree - this study aims to analyze the new professional profile proposed in curriculum pedagogy , Physical Education , Science Biology , Mathematics , Physics and Geography . Within the curriculum guidelines was observed in a more normative articulated curriculum, focused on action-reflection- action. A guided design in practical rationality and the skills set without breaking the commitment of the public university with emancipation and quality education . Although there is this understanding we must also attend to the care that must be given to the new guidelines , based on the same reveal great concern with vocational training , with its instrumentation , with the pragmatic and utilitarian dimension of the training process . It is noteworthy that throughout the twentieth century in Brazil , where he fought for educational policies that were to solidify the construction of teacher identity , but the gains have largely remained restricted to the issue of educational reforms and a roster of disciplines , called pedagogical varnish . Therefore, this work is to deepen this thematic perspective , studying the identity of the teacher in the new curriculum design presented by undergraduate courses . Therefore , the central objective seeks to understand how the identity of teacher ( professional profile ) was presented in the proposals for teacher training , as well as the different elements that make up this identity process . Specifically if you want to ( a) identify the proposals of courses for Teachers of Primary Education , UNESP / RC - Institute of Biosciences and Geosciences and Exact Sciences - Biological Sciences , Physical Education , Physics , Geography , Mathematics and Pedagogy - the proposed profile and ( b ) analyze the fundamental knowledge that this professional listing the elements...

Tendo como referência as mudanças curriculares propostas pela Resolução CNE 1/2002 e Resolução CNE 2/2002 sobre a Formação de Professores da Educação Básica, licenciatura plena - o presente trabalho visa analisar o novo perfil profissional proposto no currículo de Pedagogia, Educação Física, Ciências Biológicas, Matemática, Física e Geografia. No âmbito das orientações curriculares observou-se nos normativos um currículo mais articulado, centrado na ação-reflexão- ação. Uma concepção pautada na racionalidade prática e no conjunto de competências, sem ignorar o comprometimento da universidade pública com a emancipação e o ensino de qualidade. Embora haja esta compreensão há que se atentar também para o cuidado que se deve ter com as novas diretrizes, em função das mesmas revelarem grande preocupação com a formação profissional, com sua instrumentalização, com a dimensão pragmática e utilitária do processo formativo. Cabe ressaltar que durante todo o século XX, no Brasil, se lutou por políticas educacionais que viessem a solidificar a construção da identidade docente, mas as conquistas acabaram ficando restritas à questão das reformas do ensino e um rol de disciplinas, denominado de “verniz pedagógico”. Neste contexto este trabalho tem como perspectiva aprofundar esta temática, estudando a identidade do professor no novo desenho curricular apresentado pelos cursos de licenciatura. Assim sendo, como objetivo central busca-se compreender como a identidade de professor (perfil profissional) foi apresentada nas propostas de formação docente, bem como os diferentes elementos que compõem este processo identitário. Especificamente se quer (a) identificar nas propostas dos cursos de Formação de Professores de Educação Básica da UNESP/RC – Instituto de Biociências e Geociências e Ciências Exatas – Ciências Biológicas, Educação Física, Física, Geografia, Matemática...
Keywords: Universidade Estadual Paulista Júlio de Mesquita Filho Instituto de Biociências (Campus de Rio Claro); Universidade Estadual Paulista Júlio de Mesquita Filho Instituto de Geociencias e Ciencias Exatas; Curriculos; Professores - Formação; Educação e Estado; Identidade profissional